1994
DOI: 10.2118/23414-pa
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pore Pressure on Drilling Response in Hard Shales

Abstract: Results are presented from laboratory drilling studies of two different hard shales similar to those found in some areas ofthe North Sea. Two laboratory drilling machines with milled-tooth bits were used. Pore pressure was measured in all the experiments, and in some it was reduced to several megapascals below bottornhole pressure (BHP). Pore-pressure reduction was achieved by allowing the pore fluid to drain out of the shale while external stresses were maintained constant. The influence of BHP was studied fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The number of factors hints at the complexity of the bit/rock interaction, something which is compounded by interdependence and nonlinearity in some of these effects. 6,7,11,15,18 Laboratory studies and modeling are however unraveling this complexity.…”
Section: Background To the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The number of factors hints at the complexity of the bit/rock interaction, something which is compounded by interdependence and nonlinearity in some of these effects. 6,7,11,15,18 Laboratory studies and modeling are however unraveling this complexity.…”
Section: Background To the Methodsmentioning
confidence: 99%
“…In permeable rocks for example, overbalance pressure influences ROP, 1 giving way to a dependence on bottomhole pressure as permeability decreases. [2][3][4] Overbalance pressure effects however are subject to dynamic influences, either via filtration effects on pore pressure in the bit/rock interaction zone, 5 or via stress effects on pore pressure around the wellbore. 6 Bit cleaning effects while drilling hydratable formations in water base drilling fluids ͑''muds''͒ may also override the effects of mechanical drilling parameters, so that rock mineralogy and mud chemistry are obviously significant factors.…”
Section: Background To the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it is the absolute bottomhole pressure, independent of the far-field pore pressure that controls ROP in impermeable rocks (Gray-Stephens et al 1994).…”
Section: Impact Of Bit Design and Mud On Ropmentioning
confidence: 99%
“…A number of the early laboratory studies showed that it was the difference between the borehole pressure and the pore pressure adjacent to the workfront which controlled pressure effects on penetration rate in permeable rocks (Eckel 1958;Eenink 1959, Van Lingen 1962;Black et al 1985). In contrast, it has since been shown that in impermeable rocks, or at least in hard shales, the absolute borehole pressure controls penetration rate independent of the initial pore pressure (Gray-Stephens et al 1994). The studies investigated basalt, dolomite, limestones, sandstones, shales, and even loose sand.…”
Section: Introductionmentioning
confidence: 99%